Vertical jump and power - Darmiento, A.; Galpin, A. J.; Brown, L. E. (Strength and Conditioning Journal, 2012)
Power and jumping ability correlate with sport performance. Improving maximal force and/or velocity increases power production, and therefore theoretically enhances game play. Coaches and researchers alike acknowledge that both jumping specific (e.g., plyometrics) and nonjumping activities (e.g., resistance training) function as valuable methods of increasing power. However, their efficacy and mechanisms of adaptation are often argued. This article presents a brief overview of vertical jumping, power, training modalities and provides a sample 12-week training cycle.